Online Business Marketing Communication Strategy for Seblak Nasiracook Products in Attracting Buyer's Interest - Siregar, Jaemi Karunnisyah; Alfikri, Muhammad; Muary, Rholand (Pena Cendekia Insani, 2023)
This study is entitled